Weekend catch-up sleep and frailty in US adults: a cross-sectional study from NHANES 2017–2020 - Huan Yao; Hu Wang; Tao Li; Xia Feng; Dan Liu; Yingyue Zhang; Minling Li; Gui Xiao (BMC Public Health)
Abstract Background Frailty is an age-related condition characterized by vulnerability to adverse health outcomes. Adequate sleep may reduce frailty risk, many individuals rely on weekend catch-up sleep (WCS) to offset weekday deficits. However, the relationship between WCS and frailty remains poorly understood. This study aims to clarify the association between WCS and frailty. Methods We conducted secondary data analyses using data from 7714 adult participants in the National Health and Nutrition Examination Survey (NHANES 2017–2020). Sleep duration was assessed through self-reported questions, while frailty was evaluated using the frailty index. WCS duration was then computed as the difference between weekend and weekday sleep durations, with WCS defined as WCS duration ≤ 0 h, 0–2 h, or ≥ 2 h. A frailty index of 0.25 or greater is considered frailty. Multivariate logistic regression analyses were conducted to explore the association between WCS and frailty. Results In fully adjusted models, participants with 0–2 h of WCS had significantly lower odds of frailty (OR 0.709; 95% CI, 0.518–0.969; P = 0.035) compared to those with no WCS (≤ 0 h). However, the association was not significant for those with ≥ 2 h of WCS (OR 0.812; 95% CI, 0.550–1.200; P = 0.248). Subgroup analyses indicated no significant interaction across subgroups (P for interaction > 0.05). Limitations The cross-sectional design limits our ability to infer causality, and the reliance on self-reported sleep data may introduce measurement bias. Additionally, the frailty index, while validated, may not capture all dimensions of frailty. Future longitudinal studies with objective sleep measurements are needed to confirm these findings. Conclusions Our findings suggest that moderate WCS (0–2 h) may be associated with a lower prevalence of frailty, although the relationship is not linear and requires further investigation. These findings contribute to the emerging evidence base linking sleep patterns with frailty risk, warranting further prospective investigation.